The NTL handbook of organization development and change : principles, practices, and perspectives - Jones, Brenda B.; Brazzel, Michael. (Pfeiffer, 2014)
"This book provides an essential learning tool for both practitioners and students and presents the skills and competencies of an effective Organizational Development practitioner. It examines OD as both field and profession, and considers its history, values and ethics, and provides best practices, theories, methods, processes, and applications-contributed by a veritable "who's who" of contributors. The collection of nearly 30 chapters offers models that build effective organizations that can provide business, social, environmental, and global sustainability. It outlines the skills required to be an effective Organizational Development practitioner, highlights the importance of values and ethics, and methodically presents best practices, theories, methods, processes, and application for a new generation of OD practitioners and students faced with constantly emerging issues and changes in the workplace environment"--